Integrating Information and Communication Technologies (ICT) In Foreign Language Teacher Training: A Pathway to Modernization - Abdullaeva Dilbar Alimbaevna (Indonesian Journal Publisher, 2025)
Modernization in teacher training emphasizes updating instructional strategies, curricula, and methodologies to meet contemporary educational needs. Integrating innovative technologies enhances teaching effectiveness and student engagement, while competency-based approaches support differentiated and inclusive instruction. In this article highlights of information and communication technology (ICT) plays a crucial role in transforming education by facilitating interactive learning, distance education, and administrative efficiency. Additionally, ICT supports remote and self-paced learning, offering accessibility and flexibility, particularly in higher education. However, excites of challenges such as digital literacy gaps, inadequate infrastructure, and reliance on technology over traditional pedagogical methods persist. In rural areas, limited access to technology and internet connectivity exacerbates educational and economic disparities, restricting learning opportunities and digital engagement. Addressing these challenges requires targeted policies, infrastructure development, and continuous professional training to maximize ICT’s potential in education.